Summarizing Technique Applied by Students at The Second Grade of SMAN 3 Langsa - Nuraini (JADEs Journal of Academia in English Education, 2020)
This aim of research was to find out kinds of summarizing technique that used by students at the second grade of SMAN 3 Langsa. Summarizing technique involves stating a work paragraph and main idea, simply, briefly, and accurately. The method of this study used qualitative method with descriptive design. The subject of study was 15 students of XI IPA7. The data were collected by using observation, interview, and documentation. Based on the result of research, the researcher found that summarizing technique that used by the students at the second grade XI IPA7 SMAN 3 Langsa were Precise summarizing technique. Precise summarizing technique is to read the contents of the text as a whole then to make conclusions from the text they read by using their own language as a whole. They summarize the ideas and thoughts they have compared to using the language in the text. In addition, students were also enthusiastic in reading English text because it developed their vocabulary mastery, explained their knowledge, and trained their creative thinking skill.